2008
DOI: 10.1128/ec.00155-08
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Sib Proteins in the Regulation of Cellular Adhesion in Dictyostelium discoideum

Abstract: Molecular mechanisms ensuring cellular adhesion have been studied in detail in Dictyostelium amoebae, but little is known about the regulation of cellular adhesion in these cells. Here, we show that cellular adhesion is regulated in Dictyostelium, notably by the concentration of a cellular secreted factor accumulating in the medium. This constitutes a quorum-sensing mechanism allowing coordinated regulation of cellular adhesion in a Dictyostelium population. In order to understand the mechanism underlying this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…During slug migration, the slime sheath is synthesised continuously by pre-stalk cells and serves as a substrate for the outer cells of the slug to move on top of and get traction from. The interaction between the slug outer cells and the slime sheath involves specialised cellmatrix-adhesion molecules of the integrin family, and contacts are organised in focal adhesions that contain talin B and paxillin B (Bukharova et al, 2005;Cornillon et al, 2008;Patel et al, 2008). The sheath is stationary with respect to the substrate on which the slug moves and collapses when the slug has moved through, leaving behind a slime trail (Kessin, 2001).…”
Section: Coordination Of Collective Movement During Dictyostelium Aggmentioning
confidence: 99%
“…During slug migration, the slime sheath is synthesised continuously by pre-stalk cells and serves as a substrate for the outer cells of the slug to move on top of and get traction from. The interaction between the slug outer cells and the slime sheath involves specialised cellmatrix-adhesion molecules of the integrin family, and contacts are organised in focal adhesions that contain talin B and paxillin B (Bukharova et al, 2005;Cornillon et al, 2008;Patel et al, 2008). The sheath is stationary with respect to the substrate on which the slug moves and collapses when the slug has moved through, leaving behind a slime trail (Kessin, 2001).…”
Section: Coordination Of Collective Movement During Dictyostelium Aggmentioning
confidence: 99%
“…The Sib proteins are proposed to be functional homologs of the β-chain of integrin heterodimer in Dictyostelium, and talin A binds to all of the five Sib proteins in vitro (18). Specifically, SibA is shown to be important in cellsubstrate adhesion in the unicellular stage (17,18). We produced a double knockout mutant lacking both talin A and SibA (talin A/SibA-null) and found that they seldom produced long tails during chemotactic locomotion (Fig.…”
Section: Talin a Is Required For Normal Tail Retraction In Directed Cellmentioning
confidence: 99%
“…This is consistent with a model in which some adhesion molecules normally linked to the cortical cytoskeleton by talin A are not pulled off the substratum in talin Anull cells that keep advancing. SibA (17,18) is a candidate of such adhesion molecules. The Sib proteins are proposed to be functional homologs of the β-chain of integrin heterodimer in Dictyostelium, and talin A binds to all of the five Sib proteins in vitro (18).…”
Section: Talin a Is Required For Normal Tail Retraction In Directed Cellmentioning
confidence: 99%
“…It is likely that SadA is not the sole mediator of substrate adhesion during the vegetative stage of Dictyostelium amoebae. The Sib (similar to integrin beta) proteins, of which there are five different genes encoded in the genome, are also receptor candidates (9,10). While only two Sib proteins (A and C) are expressed during vegetative growth, all five members have been shown to interact with TalA (Dictyostelium talin homologue), which consequently has also been shown to have a role in substrate adhesion.…”
Section: Vol 10 2011mentioning
confidence: 99%
“…Intriguingly, Dictyostelium encodes a number of homologous proteins that are involved in adhesion in higher eukaryotes, such as talin, Rap1, paxillin, and others (7,21,24,32). Recently, a protein with some attributes of metazoan ␤-integrins was identified in Dictyostelium, but its placement in a cell-substrate adhesion pathway remains to be defined (9,10). These Dictyostelium proteins likewise have documented roles in adhesion.…”
mentioning
confidence: 99%